Transcatheter closure of patent foramen ovale using the Amplatzer septal occluder to prevent recurrence of neurological decompression illness in divers. Issue 3 (1st March 1999) - Walsh, K P; Wilmshurst, P T; Morrison, W L
Abstract : OBJECTIVE: Large flap valve patent foramens may cause paradoxical thromboembolism and neurological decompression illness in divers. The ability of a self expanding Nitinol wire mesh device (Amplatzer septal occluder) to produce complete closure of the patent foramen ovale was assessed. PATIENTS: Seven adults, aged 18–60 years, who had experienced neurological decompression illness related to diving. Six appeared to have a normal atrial septum on transthoracic echocardiography, while one was found to have an aneurysm of the interatrial septum. METHODS: Right atrial angiography was performed to delineate the morphology of the right to left shunt. The defects were sized bidirectionally with a precalibrated balloon filled with dilute contrast. The largest balloon diameter that could be repeatedly passed across the septum was used to select the occlusion device diameter. Devices were introduced through 7 F long sheaths. All patients underwent transthoracic contrast echocardiography one month after the implant. RESULTS: Device placement was successful in all patients. Device sizes ranged from 9–14 mm. The patient with an aneurysm of the interatrial septum had three defects, which were closed with two devices. Right atrial angiography showed complete immediate closure in all patients. Median (range) fluoroscopy time was 13.7 (6–35) minutes. Follow up contrast echocardiography showed no right to left shunting in six of seven patients and the passage of a few bubbles in one patient. All patients have been allowed to return to diving. CONCLUSION: The Amplatzer septal occluder can close the large flap valve patent foramen ovale in divers who have experienced neurological decompression illness. Interatrial septal aneurysms with multiple defects may require more than one device.